Sacks, Ed., Utopia - Wade, Harry (Teaching History: A Journal of Methods, 2000)
David Harris Sacks, professor of history and humanities at Reed College and author of two books on early modem British history, has made an important contribution to the Bedford Series in History and Culture with this edition of Sir Thomas More’s Utopia. The Bedford Series is designed to present important historical documents in a manner that helps the reader study the past as historians do. More’s widely read and highly influential Utopia is certainly an important historical document, and Sacks’s edition aids the reader in approaching the document as a historian would in several ways.